Solidarność Radia i Telewizji . [pismo członków NSZZ "Solidarność" PR i TV], no. 22, 1988 - [ed. Małgorzata Jedynak, Ewa Łubińska, Zygmunt Gutowski], [ed. committee] (Warszawa, 1988)
Creation and circulation: First two issues published in September 1980 in a few copies. The magement of Komitet do Spraw Radia i Telewizji have not allowed for publication of a trade-union journal. Publication suspended to 1981. Suspended between 13 December 1981 and October 1985